The relationship between health-related fitness and quality of life in postmenopausal women from Southern Taiwan - Hsu WH (Dove Medical Press, 2014)
Wei-Hsiu Hsu,1–3 Chi-lung Chen,2 Liang Tseng Kuo,2 Chun-Hao Fan,1 Mel S Lee,2 Robert Wen-Wei Hsu2 1Sports Medicine Center, Chang Gung Memorial Hospital at Chia Yi, Chia Yi, Taiwan; 2Division of Sports Medicine, Department of Orthopedic Surgery, Chang Gung Memorial Hospital at Chia Yi, Chia Yi, Taiwan; 3Department of Medicine, Chang Gung University, Tao Yuan, Taiwan Background: Health-related fitness has been reported to be associated with improved quality of life (QoL) in the elderly. Health-related fitness is comprised of several dimensions that could be enhanced by specific training regimens. It has remained unclear how various dimensions of health-related fitness interact with QoL in postmenopausal women.Objective: The purpose of the current study was to investigate the relationship between the dimensions of health-related fitness and QoL in elderly women.Methods: A cohort of 408 postmenopausal women in a rural area of Taiwan was prospectively collected. Dimensions of health-related fitness, consisting of muscular strength, balance, cardiorespiratory endurance, flexibility, muscle endurance, and agility, were assessed. QoL was determined using the Short Form Health Survey (SF-36). Differences between age groups (stratified by decades) were calculated using a one-way analysis of variance (ANOVA) and multiple comparisons using a Scheffé test. A Spearman’s correlation analysis was performed to examine differences between QoL and each dimension of fitness. Multiple linear regression with forced-entry procedure was performed to evaluate the effects of health-related fitness. A P-value of <0.05 was considered statistically significant.Results: Age-related decreases in health-related fitness were shown for sit-ups, back strength, grip strength, side steps, trunk extension, and agility (P<0.05). An age-related decrease in QoL, specifically in physical functioning, role limitation due to physical problems, and physical component score, was also demonstrated (P<0.05). Multiple linear regression analyses demonstrated that back strength significantly contributed to the physical component of QoL (adjusted beta of 0.268 [P<0.05]). Conclusion: Back strength was positively correlated with the physical component of QoL among the examined dimensions of health-related fitness. Health-related fitness, as well as the physical component of QoL, declined with increasing age. Keywords: postmenopausal women, health related fitness, back strength, quality of life